Students’ dance performances and the utilization of e-materials in physical education - Aguelo, Mary Jean; Aquino, John Michael (UIR Press Bekerjasama dengan International Association of Physical Education and Sports, 2023)
As a result of the Covid-19 virus, which has affected everyone, the educational community is in a tough situation right now. Technology's advancement in the teaching-learning instruction process is both a benefit and a drawback of globalization's educational approach. The study was primarily concerned with how the use of e-materials in the classroom might increase students' learning performance in physical education dancing. This study was a correlational investigation of 50 grade 9 students' dance performances and the utilization of e-materials in physical education in Sta. Catalina National High School, Candelaria, Quezon. The research was conducted using a descriptive-quantitative technique and a self-administered questionnaire through Google Form. The findings demonstrated that the use of e-materials in physical education dancing is always noted, and students' performance improves significantly when e-materials are used. Furthermore, there is no relationship between e-materials used to teach dance in physical education and student dance performance. It encouraged students to keep using and employing the effectiveness of e-materials in their dancing performances. This research will help to understand how effective the use of e-materials is in teaching dance in physical education and how it affects student performance and will provide valuable insights on the best practices for teaching dance in physical education and how to maximize the use of e-materials to enhance student performance.